Avoiding extinction: 21st century economics - Chichilnisky, Graciela (Henry Stewart Talks, 2022)
Climate change, Extinction, Survival, Western economics, Natural resources, Global commons, Kyoto Protocol, Carbon market, Water market, Green energy, CO2 pollution